Design and analysis of an aging‐aware energy management system for islanded grids using mixed‐integer quadratic programming - Kumtepeli, Volkan; Zhao, Yulong; Naumann, Maik; Tripathi, Anshuman; Wang, Youyi; Jossen, Andreas; Hesse, Holger (International journal of energy research, 2019)
Summary The rapid increase of renewable energy sources made coordinated control of the distributed and intermittent generation units a more demanded task. Matching demand and supply is particularly challenging in islanded microgrids. In this study, we have demonstrated a mixed‐integer quadratic programming (MIQP) method to achieve efficient use of sources within an islanded microgrid. A unique objective function involving fuel consumption of diesel generator, degradation in a lithium‐ion battery energy storage system, carbon emissions, load shifting, and curtailment of the renewable sources is constructed, and an optimal operating point is pursued using the MIQP approach. A systematic and extensive methodology for building the objective function is given in a sequential and explicit manner with an emphasis on a novel model‐based battery aging formulation. Performance of the designed system and a sensitivity analysis of resulting battery dispatch, diesel generator usage, and storage aging against a range of optimization parameters are presented by considering real‐world specifications of the Semakau Island, an island in the vicinity of Singapore. A systematic methodology based on mixed‐integer quadratic programming is used to build an aging‐aware energy management system for islanded microgrids. To model the storage system behavior and to enable practitioners to test and simulate their systems, an open‐source platform called SimSES is adopted. Considering the abovementioned model and algorithm, a lifetime analysis for LFP‐type lithium‐ion batteries is numerically investigated through batch simulations.